Emerging roles for the pro-oncogenic anterior gradient-2 in cancer development - Chevet E; Fessart D; Delom F; Mulot A; Vojtěšek, Bořivoj; Hrstka, Roman; Murray E; Gray T; Hupp T (Oncogene, 2013)
Clinical studies have defined the core 'genetic blueprint' of a cancer cell, but this information does not necessarily predict the cancer phenotype. Signalling hubs that mediate such phenotype have been identified largely using OMICS platforms that measure dynamic molecular changes within the cancer cell landscape. The pro-oncogenic protein anterior gradient 2 (AGR2) is a case in point; AGR2 has been shown using a range of expression platforms to be involved in asthma, inflammatory bowel disease, cell transformation, cancer drug resistance and metastatic growth. AGR2 protein is also highly overexpressed in a diverse range of human cancers and can be secreted and detected in extracellular fluids, thus representing a compelling pro-oncogenic signalling intermediate in human cancer. AGR2 belongs to the protein disulphide isomerase family with all the key features of an endoplasmic reticulum-resident protein-this gives clues into how it might function as an oncoprotein through the regulation of protein folding, maturation and secretion that can drive metastatic cell growth. In this review, we will describe the known aspects of AGR2 molecular biology, including gene structure and regulation, emerging protein interaction networks and how its subcellular localization mediates its biological functions. We will finally review the cases of AGR2 expression in human cancers, the pathophysiological consequences of AGR2 overexpression, its potential role as a tumour biomarker that predicts the response to therapy and how the AGR2 pathway might form the basis for drug discovery programmes aimed at targeting protein folding/maturation pathways that mediate secretion and metastasis.
Keywords: Animals; tamoxifen; vývojová regulace genové exprese; multigenová rodina; mapy interakcí proteinů; Biomarkers, Tumor; Humans; Gene Expression Regulation, Developmental; Neoplasms; Multigene Family; promotorové oblasti (genetika); androgeny; lidé; nádorové biomarkery; Estrogens; Extracellular Fluid; zvířata; extracelulární tekutina; transportní proteiny; Promoter Regions, Genetic; Gene Expression Regulation, Neoplastic; nádorové proteiny; Female; endoplazmatické retikulum; chemorezistence; aminokyselinové motivy; proteiny; Neoplasm Proteins; Carrier Proteins; Tamoxifen; Protein Interaction Maps; Proteins; Drug Resistance, Neoplasm; regulace genové exprese u nádorů; Endoplasmic Reticulum; ženské pohlaví; nádory; estrogeny; Androgens; Amino Acid Motifs